Painless aortic dissection with slurred speech (Neurologic symptom) - Esmaeal Rayat Dost (Journal of Emergency Practice and Trauma, 2021)
Objective: Aortic dissection is an uncommon disorder with a high mortality rate, especially if misdiagnosis and mistreatment are not considered. Case Presentation: We present a 67-year old female with slurred speech and left sided plegia during her brother’s funeral. The patient did not have any chest pain. she was referred to our emergency department by EMS due to being suspicious of cerebrovascular accident (CVA) )as code 724). However, owing to low blood pressure and atypical symptoms of the patient, we did RUSH exam in the emergency department to detect aortic dissection. After doing the Computed tomography (CT) angiography, the diagnosis of aortic dissection was confirmed. As the vascular surgeon was not present in our surgery department, we transferred the patient to Namazi hospital by air ambulance to undergo the surgery. She was discharged from hospital with complete recovery. Conclusion: Aortic dissection symptoms can be manifested in different ways such as pulmonary embolism, ACS, and CVA. Therefore, clinicians must always have the differential diagnosis of aortic dissection in their mind and be aware of its various manifestations.